Efficiency breakthrough for radical LEDs. (22nd November 2018) - Kusamoto, Tetsuro; Nishihara, Hiroshi
A strategy for using organic free radicals to make light-emitting diodes circumvents the constraints that limit the efficiency with which other organic LEDs convert electric current into light. A milestone in the development of radical-based organic LEDs.